2019
DOI: 10.3389/fneur.2019.00115
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Focal Muscle Vibration on Motor Recovery After Acute Stroke: A Pilot Randomized Sham-Controlled Study

Abstract: Repetitive focal muscle vibration (rMV) is known to promote neural plasticity and long-lasting motor recovery in chronic stroke patients. Those structural and functional changes within the motor network underlying motor recovery occur in the very first hours after stroke. Nonetheless, to our knowledge, no rMV-based studies have been carried out in acute stroke patients so far, and the clinical benefit of rMV in this phase of stroke is yet to be determined. The aim of this randomized double-blind sham-controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 37 publications
(45 reference statements)
2
35
0
3
Order By: Relevance
“…To clarify the spinal and cortical mechanisms related to visual and proprioceptive information, future studies should consider performing a detailed examination using TMS, peripheral nerve stimulation, and brain imaging methods. In addition, previous studies have suggested that therapy using motor imagery (Tabernig et al, 2018; Geiger et al, 2019) or vibration (Ahn et al, 2019; Toscano et al, 2019) could be beneficial in the neurorehabilitation of patients with stroke. Although we investigated whether the corticospinal excitabilities for reciprocal muscles were differentially affected by visuo-proprioceptive tasks, further studies should investigate whether engaging in combined observation and vibration can facilitate motor recovery of reciprocal muscles in patients.…”
Section: Discussionmentioning
confidence: 99%
“…To clarify the spinal and cortical mechanisms related to visual and proprioceptive information, future studies should consider performing a detailed examination using TMS, peripheral nerve stimulation, and brain imaging methods. In addition, previous studies have suggested that therapy using motor imagery (Tabernig et al, 2018; Geiger et al, 2019) or vibration (Ahn et al, 2019; Toscano et al, 2019) could be beneficial in the neurorehabilitation of patients with stroke. Although we investigated whether the corticospinal excitabilities for reciprocal muscles were differentially affected by visuo-proprioceptive tasks, further studies should investigate whether engaging in combined observation and vibration can facilitate motor recovery of reciprocal muscles in patients.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 12 fMV sessions (3 sessions per week for 4 consecutive weeks) were carried out by a trained physiatrist. Each daily session consisted of three 10-min treatment, interspersed with a 1-min break ( 11 ).…”
Section: Case Study—from a Vespa Scooter Ride Overmentioning
confidence: 99%
“…Focal repetitive muscle vibration (fMV) is a safe and welltolerated intervention, easy to perform at the bedside, and able to promote motor recovery both in acute (11) and chronic stroke patients (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…FMV promotes neural plasticity and long-lasting motor recovery [ 17 ]. When applied repeatedly, FMV produces a repeated sensory input that reaches the primary motor cortex (M1) directly via Ia fiber afferent input, thereby leading to an improvement in motor function by means of an intrinsic plasticity-related mechanism [ 17 , 18 , 19 , 20 ]. Recent literature has established evidence supporting the benefits of FMV in activating the primary somatosensory cortex and intensifying the connection strength of the central region [ 17 , 19 , 21 ], increasing nitric oxide production [ 22 ], improving blood flow [ 23 ], and increasing angiogenesis [ 24 ].…”
Section: Introductionmentioning
confidence: 99%